A decision system based on intelligent perception and decision for scene ventilation safety. (12th May 2021) - Li, Jingzhao; Li, Tengfei
There are many hidden safety hazards in mine ventilation process, which cannot be dealt with in time. It is because the type of coal mine and its mining conditions are complex and changeable, and the safety decision-making level is low when coal mine ventilation is abnormal. To solve these problems, this paper presents a decision system for scene ventilation safety based on intelligent perception and decision. First, grey correlation analysis and rough set theory are used to reduce the decision table horizontally and vertically. Then, the reduced data is input into the mine ventilation safety decision model based on the improved capsule network to make ventilation safety decision. Experimental results show that this system can significantly improve the accuracy of mine ventilation safety decision, has the characteristics of strong information perception ability and accurate decision, and provides an important guarantee for mine ventilation safety.